The Visual Identity of Arts and Cultural Areas Conferences for Providing Visibility - Ivanova, Irēna; Strode, Aina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
Aim of he article – to make art, music and culture conferences exploration and to analyze their importance, the visual identity and the topicality nowadays, to take a qualitative research evaluating the organized conferences in the Latvia and elsewhere in the world. In greater depth were studied the art and design research in the Latvia and in the globally. In the Article are also studied the events review of the Rezekne Higher Education Institution conference „Art and music cultural discourse” and was carried out the analysis of the visual identity in the art, music and culture conferences in the Latvian institutions of Higher Education.